Clustering Consumer Adoption Behavior with Respect to Innovative Tea Products in the Chinese Market - Han Yin; Eddy S. Fang (Beverages, 2024)
This study explores the diffusion of innovative tea products in the Chinese market, examining the shift from traditional tea consumption toward “new tea” products characterized by convenience, variety, and alignment with contemporary consumer preferences. Using a structured questionnaire, data were collected from 543 participants and analyzed through factor-cluster analysis to segment consumers based on their innovation adoption behavior. The results indicate that younger, educated, and higher-income groups adopt new tea innovations more rapidly. Notably, early adopters, representing over half of the consumer base, are not frequent consumers of these beverages, compelling suppliers to continually innovate to maintain long-term revenue growth. This study contributes to the literature by highlighting the influence of sociodemographic factors on adoption rates and offering strategic marketing insights to enhance the uptake of new tea products. These findings underscore the importance of targeting demographic segments effectively and addressing the unique consumption patterns of early adopters to drive sustained market growth.